PHOTOCHEMICAL STUDY OF THE FRACINATION OF RED SEAWEED(Eucheuma spinosum) - Wahyudi Wahyudi; Mirna Ilza Mirna Ilza; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Seaweed or known as seaweed is one of the marine organisms that has the potential as a source of bioactive, food and medicine because it contains secondary metabolites such as flavonoids, alkaloids, phenols and so on. Seaweed was obtained from Moro Island, Riau Islands, this study aims to identify the type of compound content using phytochemical test analysis. The method used in this study is a qualitative test with several reagents such as reagentsmayer, dragendorf and Wagner,using several solvents such as methanol, n-hexane, ethyl acetate and butanol. This study consisted of several stages, namely: sample preparation, extraction, fractionation and qualitative test of the bioactive compound E. spinosum whichconsists of alkaloids, flavonoids, steroids/terpenoids, saponins and phenolics. Based on the results of the study showed that red seaweed E. spinosum has bioactive compounds contained in methanol extract, namely alkaloids, flavonoids, steroids/terpenoids, and saponins, in the n-hexane fraction there are steroids/terpenoids and saponins, in the ethyl acetate fraction there are alkaloids, flavonoids, steroids/terpenoids, and saponins, then in the butanol fraction there are alkaloids and steroids/terpenoids. Keywords: Photochemical, Fraksination, Seaweed